International Business Research: Past, Present and Future - Ricks, David A. (Journal of International Business Studies, 1985)
The Editors of the Journal of International Business Studies (JIBS) always try to publish the best international business research. Unfortunately, there will probably never be a simple response to the question, What constitutes excellent international business research? We might make some progress, however, if we first attempt to define international business research and then identify several noteworthy examples.